Associations between a fatty acid desaturase gene polymorphism and blood arachidonic acid compositions in Japanese elderly. (February 2016) - Horiguchi, Sayaka; Nakayama, Kazuhiro; Iwamoto, Sadahiko; Ishijima, Akiko; Minezaki, Takayuki; Baba, Mamiko; Kontai, Yoshiko; Horikawa, Chika; Kawashima, Hiroshi; Shibata, Hiroshi; Kagawa, Yasuo; Kawabata, Terue
Abstract: We investigated whether the single nucleotide polymorphism rs174547 (T/C) of the fatty acid desaturase-1 gene, FADS1, is associated with changes in erythrocyte membrane and plasma phospholipid (PL) long-chain polyunsaturated fatty acid (LCPUFA) composition in elderly Japanese participants ( n =124; 65 years or older; self-feeding and oral intake). The rs174547 C-allele carriers had significantly lower arachidonic acid (ARA; n -6 PUFA) and higher linoleic acid (LA, n -6 PUFA precursor) levels in erythrocyte membrane and plasma PL (15% and 6% ARA reduction, respectively, per C-allele), suggesting a low LA to ARA conversion rate in erythrocyte membrane and plasma PL of C-allele carriers. α-linolenic acid ( n -3 PUFA precursor) levels were higher in the plasma PL of C-allele carriers, whereas levels of the n -3 LCPUFAs eicosapentaenoic acid (EPA) or docosahexaenoic acid (DHA) were unchanged in erythrocyte membrane and plasma PL. Thus, rs174547 genotypes were significantly associated with different ARA compositions of the blood of elderly Japanese.